Macroeconomic effects of carbon transition policies: An assessment based on the ECB's New Area-Wide Model with a disaggregated energy sector - Günter Coenen; Matija Lozej; Romanos Priftis (European Central Bank (ECB), 2023)
We use scenario analysis to assess the macroeconomic effects of carbon transition policies aimed at mitigating climate change. To this end, we employ a version of the ECB's New Area-Wide Model (NAWM) augmented with a framework of disaggregated energy production and use, which distinguishes between "dirty" and "clean" energy. Our central transition scenario is that of a permanent increase in carbon taxes, which are levied as a surcharge on the price of dirty energy. Our findings suggest that increasing euro area carbon taxes to an interim target level consistent with the transition to a net-zero economy entails a transitory rise in inflation and a lasting, albeit moderate decline in GDP. We show that the short and medium-term effects depend on the monetary policy reaction, on the path of the carbon tax increase and on its credibility, while expanding clean energy supply is key for containing the decline in GDP. Undesirable distributional effects can be addressed by redistributing the fiscal revenues from the carbon tax increase to low-income households.
Keywords: C54; E52; E62; H23; Q43; 330; Climate change; carbon taxation; DSGE model; monetary policy; fiscal policy; euro area